Intraurethral Instillation of 5-fluorouracil with Suprapubic Cystostomy for Intraurethral Condyloma Acuminatum - Jong Gyun Ha; Young Hwii Ko; Yeong Uk Kim (Urogenital Tract Infection, 2023)
Condyloma acuminatum is a common sexually transmitted disease caused by the human papillomavirus and with a high recurrence rate in the urethra. We report the intraurethral instillation of 5-fluorouracil cream for intraurethral condyloma acuminatum with suprapubic cystostomy after transurethral surgery. A 64-year-old man had gross hematuria for several days. At cystourethroscopy, multiple papillary mass lesions were identified on the entire urethra. Transurethral resection of the urethral masses confirmed the diagnosis of condyloma acuminatum. However, recurrent multiple warts were identified on the whole urethra. After re-surgery, intraurethral instillation of 5-fluorouracil cream with suprapubic cystostomy was achieved to prevent a recurrence. After one year of 5-fluorouracil instillation, there was no recurrence of intraurethral condyloma acuminatum.